A SEM-ANN-NCA ANALYSIS OF GEN Z’S PERCEPTION-DRIVEN ADOPTION OF AUGMENTED E-COMMERCE - Alfia Sayed; Asish Oommen Mathew; Lewlyn L.R. Rodrigues (Journal of Applied Structural Equation Modelling, 2025)
Grounded in the Technology Acceptance Model, Flow Theory, and Diffusion of Innovation, this paper explores the psychological indicators of Augmented Reality (AR)-enabled e-commerce adoption among Gen Z in India. It studies the direct effects of trust, compatibility, enjoyment, usefulness, ease of use, and AR perception on the intention to use such a platform. Additionally, we identify each variable's normalized relative relevance and the essential factors driving adoption. Criterion-based purposive sampling was employed to collect data from Gen Z e-commerce users across India. 658 usable responses were collected over three months. The dataset was analyzed using Partial Least Squares Structural Equation Modelling, Artificial Neural Networks, and Necessary Condition Analysis. The analysis revealed that enjoyment and compatibility are the strongest predictors of AR adoption, ranked first and second, respectively, and are a must-have with a medium effect size. Following that, ease of use and AR perception establish a significant relationship and are found to be moderately necessary. Remarkably, while trust and usefulness are statistically significant, they rank the lowest, indicating that they are foundational but not top predictors. Previous research focused on features specific to AR instead of fully grasping genuine user interaction. This research closes a significant gap in the academic discourse by providing a model for AR adoption in a developing market with factors that account for users' interaction with AR features. Investing in gamified, high-quality, and realistic AR experiences and alignment to users' lifestyles can drive adoption, leading to customer retention and loyalty.